FC 033LONG-TERM FOLLOW-UP OF PATIENTS WITH ANCA-ASSOCIATED VASCULITIS INCLUDED IN EUROPEAN VASCULITIS SOCIETY RANDOMIZED CLINICAL TRIALS SINCE 1995: A SURVIVAL ANALYSIS. (29th May 2021) - Sanchez Alamo, Beatriz; Moi, Laura; Faurschou, Mikkel; Hauser, Thomas; Bajema, Ingeborg M; Luqmani, Raashid; Mahr, Alfred; Cid, Maria; Hruskova, Zdenka; Tesar, Vladimir; Jayne, David; Westman, Kerstin W A
Abstract: Background and Aims: ANCA-associated vasculitis (AAV) is the most common cause of rapidly progressive glomerulonephritis globally and the most common finding in renal biopsies for those above 75 years of age. Patients with AAV have had an improved outcome after the introduction of immunosuppressive therapy. However, there is still an increased risk of end stage renal failure, complications to therapy, comorbidities and death. The European Vasculitis Society (EUVAS) has run several prospective randomized clinical trials (RCT) since late -90'ies as an attempt to improve the outcome for patients with a broad spectrum of AAV. The aim of the current study was to analyze results from a 10-year follow-up of patients who have participated in EUVAS's randomized clinical trials to report on patient outcomes using current standard of care immunosuppressive treatment. Method: Data on patient outcomes were collected from questionnaires to the principal investigators of the original RCTS (74 centers from 17 countries in Europe): MEPEX, NORAM, CYCAZAREM, CYCLOPS, IMPROVE, RITUXVAS and MYCYC. All patients were well characterized at inclusion in the trials respectively, as was the type and duration of induction therapy. Long-term follow-up data regarding cumulative duration and type of immunosuppressive therapy, end stage renal failure (ESRF), renal transplantation, patient survival and comorbidities as cardiovascular events, infections were recorded. Efforts have been made to control and validate the collected data. Results: The current dataset comprises 858 patients, of whom 708 were eligible to include in this study. We received questionnaires regarding patient outcomes from 70% of the cohort. The median age was 60 years at time of the diagnosis of AAV; 487 patients had GPA (57%) and 371 MPA (43%). The median follow-up time was 8.0 years (IQR: 2.9-13.6). During the observation period, there were 305 deaths: 78 patients died within the first year of follow up, 69 during the following 5 years, and another 158 patients after 5 years. The main causes of death were infections (25%), cardiovascular disease (14%) and malignancies (13%), followed by pulmonary diseases, vasculitis, others, kidney disease and gastrointestinal disease. Vasculitis were a major contributor to the causes of death in 18% of the patients. Median survival time for the whole cohort was 17.8 years (95%CI: 15.6 – 20.1). Survival rate at 5 and 10 years was 81.6% and 66.5% respectively. Advanced age, low estimated glomerular filtration rate and male sex were negative prognostic factors for patient survival in the Cox model. When we categorized the deaths according to their initial CKD stage, the highest number of deaths was found in the group of patients with low eGFR i.e. an initial CKD stage V (40%). The initial CKD stage, as shown in the Kaplan-Meier curve, was found to have an important impact on the patient survival (LR: 144.4 p<0.001). In our cohort, 159 patients (18.5%) reached ESRF, of whom 110 patients died (69%); the main cause of death in this group was infection. Conclusion: In a series of over 800 patients with AAV, ten-year mortality was predominantly associated with impaired renal function at onset, older age and male gender, rather than subtype of disease. The main strength of this study is that we have a well-defined cohort of patients with AAV, all with well-defined induction treatments and a long period of follow-up with the possibility to analyze possible prognostic factors regarding outcomes. Further analyses are ongoing regarding comparative statistics, cumulative incidence of malignancies, renal transplantation and comorbidities. The data supports efforts to diagnose these patients at an earlier stage, when they have a higher eGFR and to tailor therapy for the individual patient. Although newer treatment modalities are available, there is still a considerable morbidity and mortality in the long-term.